2013
DOI: 10.1159/000342237
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Encephalomyelitis with Rigidity and Myoclonus: A Syndrome with Diverse Clinical Features and Antibody Responses

Abstract: Background/Aims: To better characterize progressive encephalomyelitis with rigidity and myoclonus (PERM) syndrome and identify novel PERM phenotypes. Methods: The clinical features and antibody status of PERM patients were investigated using immunoblots, cell-based assays, RIA, protein macroarray and ELISA. Results: Two patients with supratentorial involvement showed abnormal PET or EEG findings. One patient was discovered to have renal cell carcinoma, and protein macroarray revealed Ma3-antibodies. Another pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 36 publications
(44 reference statements)
0
19
0
Order By: Relevance
“…LGI1 antibodies have been detected predominantly in limbic encephalitis, epilepsy and few patients with Morvan’s disease [5,13,36]. Furthermore, LGI1 antibodies were detected in a glutamic acid decarboxylase antibody-positive patient suffering from progressive encephalomyelitis with rigidity and myoclonus (PERM) [39]. …”
Section: Discussionmentioning
confidence: 99%
“…LGI1 antibodies have been detected predominantly in limbic encephalitis, epilepsy and few patients with Morvan’s disease [5,13,36]. Furthermore, LGI1 antibodies were detected in a glutamic acid decarboxylase antibody-positive patient suffering from progressive encephalomyelitis with rigidity and myoclonus (PERM) [39]. …”
Section: Discussionmentioning
confidence: 99%
“…Less frequent critical illnesses that can present with myoclonus are HIV encephalopathy (Canafoglia et al, 2003;Kanjanasut et al, 2010) and prion diseases, such as CreutzfeldtJakob disease (CJD) (Binelli et al, 2010;Chen et al, 2010). Myoclonus generated from spinal cord segments can be associated with traumatic spinal cord injury (Calancie, 2006), spinal cord tumors (Massimi et al, 2009), the Stiff-Person syndrome (Meinck et al, 1995), and with the progressive encephalomyelitis with rigidity and myoclonus (PERM) (Kraemer and Berlit, 2008;Kyskan et al, 2013;Shugaiv et al, 2013;Spitz et al, 2004).…”
Section: Symptomatic Myoclonus In the Icumentioning
confidence: 99%
“…In contrast to severe postanoxic encephalopathy where the patients' mental status persists as comatose, the majority of patients with Lance-Adams syndrome regain consciousness. Some reports suggested that ''giant" somatosensory-evoked potentials (''giant" SSEPs described subsequently), usually seen in patients with cortical myoclonus, can distinguish patients with (2008), Kyskan et al (2013), Shugaiv et al (2013) and Spitz et al (2004) Peripheral nervous system Peripheral nerve lesions Assal et al (1998) (2015) xxx-xxx severe postanoxic encephalopathy from Lance-Adams syndrome. However, there are also reports describing ''giant" SSEPs in patients with Lance-Adams syndrome (Werhahn et al, 1997).…”
Section: Cortical Myoclonus In the Icumentioning
confidence: 99%
See 1 more Smart Citation
“…Myoclonus typically involves the trunk or limbs as well as cranial-nerve innervated muscles, and is frequently stimulus-sensitive. Other brainstem signs such as nystagmus, oculomotor abnormalities, dysarthria, and dysphagia can be present, as well as cerebellar ataxia [ 108 , 109 ], cognitive impairment, encephalopathy and seizure [ 106 , 110 , 111 ]. Dipeptidyl-peptidase-like protein-6 (DPPX) [ 108 ] and glycine receptor antibodies [ 96 , 106 , 111 , 112 ] may be present, in addition to the previously mentioned anti-GAD antibodies [ 113 ].…”
Section: Reviewmentioning
confidence: 99%